2021
DOI: 10.1155/2021/1416236
|View full text |Cite
|
Sign up to set email alerts
|

Acupoint Massage Therapy Alters the Composition of Gut Microbiome in Functional Constipation Patients

Abstract: Objective and Background. Constipation is under high incidence globally. Current drug treatment on constipation, especially chronic functional constipation (CFC), lacks of efficiency and has an adverse reaction. Acupoint Massage Therapy (AMT) is traditionally applied to CFC with a good success rate and without unfavorable reaction in China. The underline mechanism of AMT remains unclear. Recent studies revealed that gut microbiome is involved in constipation development and treatment. Our aim is to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Acupoint sticking therapy for constipation involves laxative action as well as the use of acupoints. A clinical study confirmed that acupoint therapy changed the composition of intestinal microflora related to cytokines in constipated patients and relieved constipation symptoms (85).…”
Section: External Treatment With Tcmmentioning
confidence: 83%
“…Acupoint sticking therapy for constipation involves laxative action as well as the use of acupoints. A clinical study confirmed that acupoint therapy changed the composition of intestinal microflora related to cytokines in constipated patients and relieved constipation symptoms (85).…”
Section: External Treatment With Tcmmentioning
confidence: 83%
“…The intestinal flora is a critical factor influencing the fitness of the intestine and body health, which could be affected by not only food or medicine intake but also massage, acupuncture [ 24 , 25 ]. Previous studies suggested that the intestinal flora plays a crucial role in wound healing, which is one of the major aetiological factors of POI.…”
Section: Discussionmentioning
confidence: 99%
“…Functional constipation (FC) is a common clinical condition and a digestive disorder with a high global prevalence that is mainly induced by non-systemic diseases or organic changes in the intestinal tract and characterized by difficulty in defecation, reduced frequency of defecation or a sense of incomplete defecation [ 1 , 2 ]. A study by Chen et al [ 3 ] suggests that approximately 20–25% of the population is affected by constipation, with more female victims and a male-to-female ratio of 1:2.2. The prevalence of functional constipation in China is about 6% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%